Mendiagnosa Penyakit pada Ayam Petelur Menggunakan Metode Certainty Factor - Sartika Nasution (Sci-tech Journal (STJ), 2022)
The nutritional status of chickens has a major effect on productivity and it is closely related to the health of chickens. Several diseases in chickens have an economic impact because they can reduce the quality of good chicken eggs to the detriment of farmers. The main problem which is the toughest challenge in chicken farming is the emergence of disease, so its management needs to be done efficiently and professionally. However, farmers usually only know the symptoms that occur in sick chickens, without knowing what disease they are suffering from. As for veterinarians, it is difficult to find, and it takes a long time to handle chickens because the cage is far from residential areas. The Certainty Factor method can be applied to diagnose laying hens disease based on the symptoms of laying hens. Based on the results of the CF calculation, the diagnosis of Avian Encephalomyelitis (AE) in red laying hens with a confidence value of 0.9654 × 100% or 96.54% and calculated with the value of Avian Influenza / Bird Flu with a confidence value of 0.6 × 100% or 60%. Thus, red chicken A is said to be diagnosed with Avian Encephalomyelitis (AE) with a Certainty Factor confidence value of 96.54%. Handling for AE disease is AE vaccination using MEDIVAC AE-Pox at the age of 10-14 weeks. With the application of giving through a wing web. Key words : Laying hens, Certainty Factor